2022
DOI: 10.1093/intqhc/mzac094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the physical therapy–managed spinal orthoses program on cost of care in the hospital setting: a retrospective interrupted time-series study

Abstract: Background The physical therapy department at a level 1 trauma center identified vendor delivery delays of off-the-shelf (OTS) spinal orthoses that delayed patient mobilization. This study aimed to identify improvements in mobilization times, discharge times, and reduction in the cost of care after centralizing the management of orthoses within the therapy department. Methods The centralized management of OTS spinal orthoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…When considering only patients who did not experience a complication, this study identified a reduced length of stay for patients managed under the centralized program. These observations agree with findings previously reported in the literature that show early ambulation with a spinal orthotic can help to decrease a patient's length of stay ( Hoyer et al, 2016 ; Stethen et al, 2018 ; Willey et al, 2022 ). A reduction in the number of inpatient days results in decreased risk of infection and medication side effects, improvement in the quality of treatment, and increased hospital profitability margins with more efficient bed management ( Baek et al, 2018 ; Horn et al, 2018 ; Lakomkin and Hadjipanayis, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…When considering only patients who did not experience a complication, this study identified a reduced length of stay for patients managed under the centralized program. These observations agree with findings previously reported in the literature that show early ambulation with a spinal orthotic can help to decrease a patient's length of stay ( Hoyer et al, 2016 ; Stethen et al, 2018 ; Willey et al, 2022 ). A reduction in the number of inpatient days results in decreased risk of infection and medication side effects, improvement in the quality of treatment, and increased hospital profitability margins with more efficient bed management ( Baek et al, 2018 ; Horn et al, 2018 ; Lakomkin and Hadjipanayis, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…While a possibility, the risk of such an occurrence is equally distributed between the two study groups. While risks of bias are always present in retrospective studies, the results reported from this study are similar to those of comparable studies ( Hanson et al, 2019 ; Willey et al, 2022 ). This study also did not evaluate patients managed conservatively with only an orthosis; however, the observed improvements in time to mobilization and length of stay following surgery likely extend to patients managed conservatively.…”
Section: Limitationssupporting
confidence: 89%
See 3 more Smart Citations